Karakter Yang Dominan Muncul Pada Siswa-Siswi SMPIT Arrisalah Pejagoan Melalui Pendidikan Karakter Menghafal Al-Qur’an - Muntaha, Deta; Chamidi, Agus Salim; Soleh, Agus Nur (Tarbi: Jurnal Ilmiah Mahasiswa, 2022)
Abstrack The purpose of this study is to analyze the process of learning to memorize the Qur’an at SMPIT Arrisalah Pejgaoan and the dominant character values emerged through the process of learning to memorize the Qur’an at SMPIT Arrisalah Pejagoan. This research is a field research conducted at SMPIT Arrisalah Pejagoan with a qualitative approach. By using a qualitative approach, and using data colletion techniques of observation, intervies, and documentation. The result of study found that the learing process of Tahfidz at SMPIT Arrisalah uses the tikrar method, namely repeating readings. The Tahfidz program is held every Monday – Thursday. Ofteh it is done during the day and for the morning it is done one Wednesday. Before depositing by rote, eachstudent ist required to be murajaah and is targeted to memorize one page 4 times a deposit. The dominant character that appears according to students and students is positive thingking, sincere, independent, patient, and honest, but there is a dominant character based on the general view, namly positive thingking and patience. Keywords : Character Education, Memorizing Al-Qur’an, Student Charcte